Context in English Language Teaching Program: Differentiating between Iranian Public Schools and Private Institutes - Hooshang Khoshsima; Seyyed Morteza Hashemi Toroujeni (Journal of English Language Teaching and Linguistics, 2017)
For some years, there was a debate about the effectiveness of public and private sectors in language learning field, not only in Iran but also in USA and Europe. Actually, a context in which language learners are provided with friendly communicative environment is a great help to learn how to use the language communicatively in authentic situations. Therefore, a context in which the efficient factors are employed more appropriately enables EFL learners to emphasize the communicative use of language in everyday, real world situations. In Iran, the students can learn English in two contexts including a) public schools that are funded and supported by the government b) private institutes. In public education, the students start learning English from the first year of Junior Secondary Program for six years. But after graduating from high school, hardly some of them are able to communicate fluently (Safari & Rashidi, 2015). Thus, this study investigated the comparability of the effectiveness of two education systems applied in two contexts on oral communication skills. Direct observations, interviews, and FCE speaking test taken by 154 students of two contexts revealed that the language learners of private institutes outperformed on oral skills. Furthermore, the results of independent t-test indicated that 8 internal and external moderator-factors assessed by a questionnaire might affect speaking performance of language learners in two contexts. The findings were also supported by the interview-based data.